Pharyngeal and peritonsillar abscess due to Leclercia adecarboxylata in an immunocompetant patient - Rishi Bali; Parveen Sharma; Komal Gupta; Saurabh Nagrath (Journal of Infection in Developing Countries)
Leclercia adecarboxylata was isolated in pure culture from a peritonsillar and lateral pharyngeal abscess in an immunocompetent host. To our knowledge, this is the first case of infection caused by this microorganism being found in an odontogenic area of the head and neck.